2014
DOI: 10.3329/cmoshmcj.v13i2.21059
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Pregnant Women Regarding Pregnancy and Safe Delivery in Selected Rural Area

Abstract: Objective: This cross sectional descriptive study was conducted to explore awareness level of pregnant women regarding pregnancy and safe delivery in selected rural area. Methodology: This community based cross sectional descriptive study was carried out at Ullapara Upazila, Sirajgonj District among 120 pregnant women in a rural community. Non probability sampling technique and pretested semistructured questionnaire was used to collect data. Results: Majority of the respondents (65 %) were between 20-34 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Similar to our ndings, another study in Matlab, Bangladesh, reported that only 26% of women had good knowledge of pregnancy complications [15]. Several studies have showed that ANC utilization is associated with women's knowledge about pregnancy complications [15,60,61]. Women with poor knowledge of pregnancy complications are likely to also be unfamiliar with the consequences of the conditions.…”
Section: Name Of Health Facilitysupporting
confidence: 86%
“…Similar to our ndings, another study in Matlab, Bangladesh, reported that only 26% of women had good knowledge of pregnancy complications [15]. Several studies have showed that ANC utilization is associated with women's knowledge about pregnancy complications [15,60,61]. Women with poor knowledge of pregnancy complications are likely to also be unfamiliar with the consequences of the conditions.…”
Section: Name Of Health Facilitysupporting
confidence: 86%
“…Low financial stability indexes, a lack of schooling, and unemployment are the main factors that cause lower DD in Bangladesh (Kundu et al, 2021). Pregnancy complications are the main reason for 99% of maternal deaths in developing or low-income nations (Hossain et al, 2014). In developing nations, women who live in rural areas have higher rates of maternal mortality than in urban areas (Castillo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In developing nations, women who live in rural areas have higher rates of maternal mortality than in urban areas (Castillo et al, 2017). According to a study, 194 maternal deaths occur for every 10,000 pregnant women in Bangladesh (Hossain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%